Kinerja Dosen terhadap Proses Pembelajaran di Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci - Saaduddin Saaduddin (Departement of Mathematics Education, 2022)
Along with the rapid development of the times, at the same time the construction industry has also grown rapidly. Along with the development of that era, the technology and construction methods in the world are increasingly developing. This also applies in Indonesia, construction methods in Indonesia are also developing. One form of the development of construction methods in Indonesia is the precast construction method. This study aims to determine how much the costs and how long it takes to implement the Cast In Situ and Precast Methods of columns and beams.The method used in this research is a quantitative method using the calculation of SNI 7394: 2008